Banks’ reserve management, transaction costs, and the timing of Federal Reserve intervention - Bartolini, Leonardo; Bertola, Giuseppe; Prati, Alessandro (Journal of Banking & Finance, 2001)
We use daily data on bank reserves and overnight interest rates to document a striking pattern in the high-frequency behavior of the US market for federal funds: depository institutions tend to hold more reserves during the last few days of each “reserve maintenance period”, when the opportunity cost of holding reserves is typically highest. We then propose and analyze a model of the federal funds market where uncertain liquidity flows and transaction costs induce banks to delay trading and to bid up interest rates at the end of each maintenance period. In this context, the central bank’s interest-rate-smoothing policy causes a high supply of liquid funds to be associated with high interest rates around reserve-settlement days.